IMAGE PROCESSING BASED ON AVIATION NAVIGATION EQUIPMENT MONITORING - Arif Sulaiman, Muhammad
Ground navigation equipments play important role in aviation world. Layered monitoring is a mandatory to ensure work of equipment. The existing monitoring system available is expensive and need high speed connection while the total airport in Indonesia is 367 spreaded over 34 provinces. With the contours of Indonesia’s territority, it will be difficult to implement. Image processing itself is often used in many sectors and widely used by academics however, its usage is still rare in aviation sector especially for aviation navigation field. The author tries to combine between image processing ability with equipment monitoring needs. To reach this goal then Raspberry Pi will be used as processing center. Aviation navigation equipment is designed and equipped with Built in Monitor in the form of a panel with indicators and some use screen. This Built in Monitor is used so that the technician can find out equipment condition faster and take action if any problem occur. Therefore, this built in monitor must be well calibrated for accurately of information. The author tries to take advantage of the Built in Monitor with process the image. Thus, the information in indicator form transform into data bits and can be visualized. The Built in Monitor has installed AprilTag fiducial marker to define the region and type of equipment to be detected. A series of images captured by the camera is first corrected to the perspective of the camera and then segmented. The results of this segmentation are classified based on the euclian distance to the reference then matched distance is converted to boolean value and sent to SQL server. To allow user can read the result of processing easily, the SQL data is processed and then displayed in website form that could be accessed anywhere. By using image processing, this design does not need to be electrically connected to the monitored equipment and can be used on all aviation navigation equipment that uses that Built in Monitor. In addition, data processing allows this design to work at a connection speed of 100 B/s. Thus, it can be implemented in areas with limited connection speeds.